1985
DOI: 10.1161/01.cir.71.6.1146
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, angiographic, and electrophysiologic findings in patients with aborted sudden death as compared with patients with sustained ventricular tachycardia after myocardial infarction.

Abstract: After the acute phase of myocardial infarction, patients who develop sustained ventricular arrhythmias present with either sudden death or ventricular tachycardia (VT). Although current evidence suggests that VT frequently precedes ventricular fibrillation (VF) in patients presenting with sudden death, the factors resulting in rapid deterioration of VT to VF have not been delineated in humans. To determine whether left ventricular function, coronary anatomy, or electrophysiologic characteristics could differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Among these mechanisms, delayed afterdepolarizations (DADs) play an important role, especially in arrhythmias associated with catecholamine-excess,10, 11 heart failure,12-14 and mutations of the ryanodine receptor or calsequestrin 15. These arrhythmias can be benign or lethal in nature depending on their hemodynamic consequence, which is regulated by various factors, including their duration and ventricular rate, that is, sustainability and frequency 16, 17. While it has been reported that the sustainability and frequency of re-entrant arrhythmias are at least in part determined by the wavelength of re-entering impulse and the circuit path,18 what determines the sustainability and frequency of triggered arrhythmias remains to be established 19, 20…”
Section: Introductionmentioning
confidence: 99%
“…Among these mechanisms, delayed afterdepolarizations (DADs) play an important role, especially in arrhythmias associated with catecholamine-excess,10, 11 heart failure,12-14 and mutations of the ryanodine receptor or calsequestrin 15. These arrhythmias can be benign or lethal in nature depending on their hemodynamic consequence, which is regulated by various factors, including their duration and ventricular rate, that is, sustainability and frequency 16, 17. While it has been reported that the sustainability and frequency of re-entrant arrhythmias are at least in part determined by the wavelength of re-entering impulse and the circuit path,18 what determines the sustainability and frequency of triggered arrhythmias remains to be established 19, 20…”
Section: Introductionmentioning
confidence: 99%
“…Electrophysiological studies have suggested a greater risk for SCA among those with ischemic cardiomyopathy who have multiple areas of transmural infarction when compared to those with less extensive scars(36). In nonischemic cardiomyopathy the presence of midwall fibrosis has been reported to predict those at risk SCA(37).…”
Section: Myocardial Scar and The Risk Of Scamentioning
confidence: 99%
“…Ischemic cardiomyopathy (i.e., infarct-related) VT is the most frequent clinical ventricular arrhythmia, present in 64% of patients with ventricular rhythm disorder and in 89% of patients with sudden cardiac death (Stevenson et al, 1985). Recently, the peri-infarct (border) zone surrounding the necrotic scar, also known as GZs, as indicated above, based on its appearance as a region of intermediate intensity in the LGE-MRI scans, has been shown to correlate with post-MI mortality (Yan et al, 2006), clinical VT (Roes et al, 2009), and VT inducibility (Schmidt et al, 2007).…”
Section: Ischemic Cardiomyopathy Remodeling In the Ventricles And Itsmentioning
confidence: 99%